Au seuil de la classe, le maître E régule différentes temporalités - Pascale Ponté; Serge Thomazet; Corinne Mérini (Recherches en Éducation)
In France, new texts reorganize how special needs at school are dealt with. These evolutions justified a research we led for three years on the work of special need teachers in charge of the learning support (maître E in French) and its vectors of transformations. We introduced here a part centered on the management of the temporality. The construction of object and methodology were structured by mobilizing the sociology of organizations and ergonomic psychology; which is interwoven with philosophy. The methodology lays on group work. The analysis of professional documents allowed us to spot « professional points of tension” that we investigated in a more detailed way during self confrontation and crossed confrontations. Our results show that special need teachers stand on the classroom door step but at the heart of collaborative work schemes and develop appropriate strategies to answer the conflicts of temporality generated by prescriptions